Consensus of Democracy in Making The National Development (Case Study of Dynamics Conflict of Selection of The Message Village Head in Blitar District) - Anwar Samaudin (Journal of Development Research, 2018)
This research is based on the simultaneous election of village heads in 2013. This phenomenon arises because of the local government policy to hold simultaneous village head elections in Blitar regency. This study aims to determine the description of conflict of simultaneous village head election in Blitar Regency followed by 150 villages. This research was conducted in eight villages of Blitar Regency. This research uses qualitative method, and described descriptively with data source in this research consist of 8 candidate of village head, some support from eight candidate of village head who has conflict. Data collection techniques used are observation, interview and documentation. Sampling technique used in this research is purposive sampling. The validity of the data in this study using triangulation techniques sources and data analysis using interactive Miles and Huberman. The result of the research shows that the conflict of simultaneous village head election in Blitar Regency that varied from the couple of husband and wife, the candidate pair from the messenger or the right hand of one candidate, the existence of some cheating in the election process, the candidate of the headache is sick to death, self. The conflicts are caused by several factors such as the absence of the candidates who register until the time limit is set, the public expectation of the leadership of one of the candidates, and the simultaneous village head election conflict in Blitar Regency are ridden by other interests, there are those who do not like one of the candidates village head. Forms of conflict that occurred in Blitar district that is the latent conflict that already exists between the two candidates for village head, manifest conflict is a riot in the form of filing a lawsuit, there is also a vertical conflict between one candidate with the supporters of the opposing party and also horizontal conflict that is between supporters.